Dimensi Patient Safety Briefing dan Dampak bagi Budaya Keselamatan Pasien - Megawati Megawati; Luky Dwiantoro; Septo Pawelas Arso (Journal of Telenursing (JOTING), 2023)
This research aims to provide a comprehensive overview of the dimensions of patient safety briefings implemented in clinical settings in hospitals and their impact on the dimensions of safety culture. This research is a scoping review using a literature search through the Scopus, CINAHL, and Medline databases. Research results, of the 472 research articles identified, 20 of them met the inclusion criteria. The research article describes the dimensions of patient safety briefings and dimensions of patient safety. Data from the results of the scoping review explains the implementation of patient safety briefings and the positive impact on the dimensions of safety culture in clinical settings in hospitals. In conclusion, complex research describes the dimensions of patient safety briefings in clinical care settings. This dimension explains the steps on how to carry out a standard patient safety briefing in a hospital clinical setting or clinical service. Empirical research regarding the dimensions of patient safety briefings has an impact on patient safety culture and improves patient safety in the context of hospital risk management. The potential for future research is to examine more broadly each dimension of patient safety briefings and their impact on clinical settings in hospitals. Key words: Patient safety briefings; Situational Awareness; Safety Culture; Hospital; Clinical Setting